New Insights Into the Role of Placental Aquaporins and the Pathogenesis of Preeclampsia - Szpilbarg, Natalia; Martínez, Nora A.; Di Paola, Mauricio; Reppetti, Julieta; Medina, Yollyseth; Seyahian, Abril; Castro Parodi, Mauricio; Damiano, Alicia E. (Frontiers in Physiology, 2018)
Accumulated evidence suggests that an abnormal placentation and an altered expression of a variety of trophoblast transporters are associated to preeclampsia. In this regard, an abnormal expression of AQP3 and AQP9 was reported in these placentas. Recent data suggests that placental AQPs are not only water channel proteins and that may participate in relevant processes required for a normal placental development, such as cell migration and apoptosis. Recently we reported that a normal expression of AQP3 is required for the migration of extravillous trophoblast (EVT) cells. Thus, alterations in this protein might lead to an insufficient transformation of the maternal spiral arteries resulting in fluctuations of oxygen tension, a potent stimulus for oxidative damage and trophoblast apoptosis. In this context, the increase of oxygen and nitrogen reactive species could nitrate AQP9, producing the accumulation of a non-functional protein affecting the survival of the villous trophoblast (VT). This may trigger the exacerbated release of apoptotic VT fragments into maternal circulation producing the systemic endothelial dysfunction underlying the maternal syndrome. Therefore, our hypothesis is that the alteration in the expression of placental AQPs observed at the end of gestation may take place during the trophoblast stem cell differentiation, disturbing both EVT and VT cells development, or during the VT differentiation and turnover. In both situations, VT is affected and at last the maternal vascular system is activated leading to the clinical manifestations of preeclampsia.